Evaluation of the publication status of dissertations of the faculty of medicine anatomy department in scientific journals (Annals of Medical Research, 2022)
Aim: The aim of this study was to evaluate the publication status of medical dissertations published by the Medical Anatomy Departments of medical faculties in our country  between 2007-2017 in scientific journals.Materials and Methods: Using the research model in September 2020, the study included a total of 57 anatomy dissertations on the internet database of the National Theses Center of the Council of Higher Education, which were registered in the system by the Anatomy Departments of all medical faculties in our country between 2007 and 2017. These dissertations were analyzed and evaluated in terms of the year they were written, the institution where they were written, the academic title of the thesis advisor, the type of research of the thesis, publication status, characteristics of the publication, gender of the author and other characteristics of the authors. SPSS v.25 software was used for statistical analysis.Results: In our study, 37 (64.9%) of the 57 anatomy dissertations written between 2007 and 2017 were published in a journal, while 20 (34.1%) were not published. Of the published dissertations, 31 (54.4%) were published in SCI/SCI-E, 5 (8.8%) in Tubitak/Ulakbim TR index, and 1 (1.8%) in other international indexes (p = 0.00).Conclusions: In this study, the conversion status of the medical dissertations that were written after the completion of anatomy specialty training in Turkey into publications and their publication rates in SCI/SCI-E  journals as articles were quite high.
Keywords: Anatomy; specialty theses; publication; Turkey